Entrepreneurship in the creative industries : how innovative agents, skills and networks interact /: how innovative agents, skills and networks interact. (2023) - McIntyre, Phillip, 1953-; Fulton, Janet, 1964-; Kerrigan, Susan; Meany, Michael (Michael M.)
No abstract available